SMPX Deficiency Causes Stereocilia Degeneration and Progressive Hearing Loss in CBA/CaJ Mice - Tu, Hailong; Zhang, Aizhen; Fu, Xiaolong; Xu, Shiqi; Bai, Xiaohui; Wang, Haibo; Gao, Jiangang (Frontiers in Cell and Developmental Biology, 2021)
The small muscle protein, x-linked (SMPX) encodes a small protein of 88 amino acids. Malfunction of this protein can cause a sex-linked non-syndromic hearing loss DFNX4. Herein, we reported a point mutation and a frameshift mutation in two Chinese families who developed gradual hearing loss with age. To explore the impaired position in the hearing system and the mechanism of DFNX4, we established and validated an Smpx null mouse using CRISPR-Cas9. By analyzing auditory brainstem response (ABR), male Smpx null mice showed a progressive hearing loss starting from the third month and high frequency. Hearing loss in female mice was milder, and it occurred later than in male mice. This audiogram is very familiar to that in human beings. Through some morphological analysis of mice cochleas, we found the hair cell bundles progressively degenerated from the shortest row. Cellular edema occurred at the end phase of ciliary degeneration, followed by cell death. By transfecting exogenous fluorescent Smpx in living hair cells, we detected it expressed in stereocilia. Through external stimulus, we found that Smpx may participate in maintaining hair cell stereocilia. We believe that this Smpx knock-out mouse may be used as a suitable model to explore the pathology of DFNX4.